C‐Plasma of Hierarchical Graphene Survives SnS Bundles for Ultrastable and High Volumetric Na‐Ion Storage. Issue 49 (9th October 2018) - Chao, Dongliang; Ouyang, Bo; Liang, Pei; Huong, Tran Thi Thu; Jia, Guichong; Huang, Hui; Xia, Xinhui; Rawat, Rajdeep Singh; Fan, Hong Jin
Abstract: Tin and its derivatives have provoked tremendous progress of high‐capacity sodium‐ion anode materials. However, achieving high areal and volumetric capability with maintained long‐term stability in a single electrode remains challenging. Here, an elegant and versatile strategy is developed to significantly extend the lifespan and rate capability of tin sulfide nanobelt electrodes while maintaining high areal and volumetric capacities. In this strategy, in situ bundles of robust hierarchical graphene ( h G) are grown uniformly on tin sulfide nanobelt networks through a rapid (5 min) carbon‐plasma method with sustainable oil as the carbon source and the partially reduced Sn as the catalyst. The nucleation of graphene, CN (with size N ranging from 1 to 24), on the Sn(111) surface is systematically explored using density functional theory calculations. It is demonstrated that this chemical‐bonded h G strategy is powerful in enhancing overall electrochemical performance. Abstract : Hierarchical graphene bundled tin sulfide (SnS) is fabricated by an ingenious in situ C‐plasma route and tested as a flexible anode for sodium‐ion batteries with unprecedented cycling lifespan, maintaining ultrahigh areal and volumetric capacities. Density functional theory calculation verifies the formation mechanism of graphene by catalysis of Sn.